Angiographic assessment of vein of Marshall in atrial fibrillation: Implications for identification and cannulation - Hong-Da Zhang; Lei Ding; Feng-Yuan Yu; Li-Jie Mi; Kuo Zhang; Si-Xian Weng; Zi-Han Jiang; Min Tang (Heliyon, 2023)
Background: The vein of Marshall (VOM) ethanol infusion improves rhythm control in atrial fibrillation (AF). The identification and cannulation of the VOM can be technically challenging. This study aimed to assess the angiographic morphology of the VOM and investigate its value in the VOM ethanol infusion. Methods: Patients with AF (n = 162) scheduled for combined catheter ablation and VOM ethanol infusion were enrolled. The VOM morphologic features in the right anterior oblique (RAO), the left anterior oblique (LAO), and the LAO cranial views were analyzed. The impact of morphology on the identification and cannulation of the VOM was investigated. Results: The VOM was identified in 159 (98.1 %) and cannulated in 150 (92.6 %) patients. The VOM identification rate in the RAO and LAO/LAO cranial view was 97.3 % and 89.3 %, respectively. Of 134 patients with VOM identification in the LAO/LAO cranial view, 104 (77.6 %) had a VOM ostium clock location (VOMoClock) of ≤3 and 3–4 o'clock. The VOM cannulation success rate in the ≤3, 3–4, 4–5, and 5–6 o'clock groups was 100 %, 92.6 %, 88.5 %, and 77.8 %, respectively (p = 0.032). The median (interquartile range) cannulation time in the four groups was 10.5 (6.3), 12.0 (9.0), 13.0 (23.0), and 34.0 (30.0) minutes, respectively (p < 0.001). The diameter of the coronary sinus ostium in the RAO view and the VOMoClock were independent predictors for difficult cannulation. Conclusions: The VOM morphologic features in different angiographic views provide valuable information which could facilitate the identification and cannulation of the VOM.